Model Peningkatan Citra dan Penguatan Produk Unggulan Desa Cileles Kecamatan Jatinangor Kabupaten Sumedang - Mohamad Ali Fulazzaky; Dede Kardaya (UNISBA Press, 2024)
Abstract. The article aims to explain the model of improving the village image through strengthening village superior products by evaluating typical MSME products of Cileles Village, Sumedang Regency. The study was conducted using empirical studies through observation and mingling with the community and participating in various economic improvement activities, especially in strengthening village products. The results of this study show that Sumedang Regency already has many achievements in government management, especially in handling stunting, which has made Sumedang Regency a model for other regions in Indonesia. The commitment of the Regional Government of Sumedang Regency in improving village economic products which is encouraged by various policies and programs in collaboration with various parties including in Cileles Village, Jatinangor District can support the development of MSMEs and village superior products, one of which is Lesmons. The implementation of a well-planned MSME program will have an impact on improving the community's economy, increasing local taxes and is also expected to improve both the image of Cileles Village and Sumedang Regency. Abstrak. Artikel bermaksud untuk menjelaskan model peningkatan citra desa melalui penguatan produk unggulan desa dengan mengevaluasi produk-produk UMKM khas Desa Cileles Kabupaten Sumedang. Kajian dilakukan dengan menggunakan studi empiris melalui observasi dan berbaur bersama masyarakat serta mengikuti berbagai kegiatan peningkatan perekonomian khususnya dalam penguatan produk desa. Hasil penelitian ini menunjukkan bahwa Kabupaten Sumedang sudah memiliki banyak prestasi dalam pengelolaan pemerintahan terutama dalam penanganan stunting yang menjadikan Kabupaten Sumedang sebagai percontohan bagi wilayah lain di Indonesia. Komitmen Pemerintah Daerah Kabupaten Sumedang dalam peningkatan produk ekonomi desa yang didorong dengan berbagai kebijakan dan program berkolaborasi dengan berbagai pihak termasuk di Desa Cileles Kecamatan Jatinangor dapat mendukung pengembangan UMKM dan produk unggulan desa yang salah satu produknya adalah Lesmons. Pelaksanaan program UMKM yang terencana dengan baik akan berdampak pada peningkatan perekonomian masyarakat, peningkatan pajak daerah dan juga diharapkan dapat meningkatkan baik citra Desa Cileles dan Kabupaten Sumedang.